Effects of air-abrasion pressure on the resin bond strength to zirconia: a combined cyclic loading and thermocycling aging study - Eman Z. Al-Shehri; Afnan O. Al-Zain; Alaa H. Sabrah; Sarah S. Al-Angari; Laila Al Dehailan; George J. Eckert; Mutlu Özcan; Jeffrey A. Platt; Marco C. Bottino (Korean Academy of Conservative Dentistry, 2017)
Objectives To determine the combined effect of fatigue cyclic loading and thermocycling (CLTC) on the shear bond strength (SBS) of a resin cement to zirconia surfaces that were previously air-abraded with aluminum oxide (Al2O3) particles at different pressures. Materials and Methods Seventy-two cuboid zirconia specimens were prepared and randomly assigned to 3 groups according to the air-abrasion pressures (1, 2, and 2.8 bar), and each group was further divided into 2 groups depending on aging parameters (n = 12). Panavia F 2.0 was placed on pre-conditioned zirconia surfaces, and SBS testing was performed either after 24 hours or 10,000 fatigue cycles (cyclic loading) and 5,000 thermocycles. Non-contact profilometry was used to measure surface roughness. Failure modes were evaluated under optical and scanning electron microscopy. The data were analyzed using 2-way analysis of variance and χ2 tests (α = 0.05). Results The 2.8 bar group showed significantly higher surface roughness compared to the 1 bar group (p < 0.05). The interaction between pressure and time/cycling was not significant on SBS, and pressure did not have a significant effect either. SBS was significantly higher (p = 0.006) for 24 hours storage compared to CLTC. The 2 bar-CLTC group presented significantly higher percentage of pre-test failure during fatigue compared to the other groups. Mixed-failure mode was more frequent than adhesive failure. Conclusions CLTC significantly decreased the SBS values regardless of the air-abrasion pressure used.